1992
DOI: 10.1159/000217779
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Pancreatic Secretory Trypsin Inhibitor Expression in Pulmonary Adenocarcinoma: Its Possible Participation in Scar Formation of the Tumor Tissues

Abstract: The expression of pancreatic secretory trypsin inhibitor (PSTI) was examined immunohistochemically in pulmonary adenocarcinoma. Of 86 carcinomas examined, 65 (76%) showed immunoreactivity for PSTI. Cases with the papillary subtype and those with early stage disease contained PSTI in cancer cells more frequently and were more strongly positive. There was a slight tendency to strong expression of PSTI in cases with the histologically well-differentiated type, tumor size of approximately 30 mm maximum diameter, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…SPINK1 is also produced in cancers of the colon (15,16), lung (17,18), liver (19), breast (20), prostate (21), and pancreas (20,22). In colon cancer, Gouyer and colleagues (23) identified and characterized SPINK1 as a major proinvasive secreted factor from the conditioned medium of HT-29 5M21 human colon cancer cells, which express a spontaneous invasive phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…SPINK1 is also produced in cancers of the colon (15,16), lung (17,18), liver (19), breast (20), prostate (21), and pancreas (20,22). In colon cancer, Gouyer and colleagues (23) identified and characterized SPINK1 as a major proinvasive secreted factor from the conditioned medium of HT-29 5M21 human colon cancer cells, which express a spontaneous invasive phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Although scar cancers of the lung have been recognized for several decades, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] a direct mechanistic association between the scar itself and the tumor has not been documented. Because no direct evidence has been observed for a causal association between the presence of scar tissue and cancer, several relatively recent publications have refuted the concept that pulmonary scars can be causal in lung cancer.…”
mentioning
confidence: 99%
“…In spite of these limitations, in some reports there is evidence that the scar (and scarring process) predates the tumor, [6][7][8][9][10][11] in others it is impossible to tell, 12,13 and in others there is evidence that there was an active scarring process as a result of the tumor. 2,3,5,[14][15][16] The basic assumption behind any conclusions of no association between a pulmonary scar and its "associated" tumor [1][2][3][4][5] is that the scar itself cannot have directly caused the tumor. In one article, 4 the authors even ruled out tuberculosis as a contributing cause even though 10 of 49 cancer patients had tuberculosis that predated the cancer.…”
mentioning
confidence: 99%
“…Its role has been considered to be a specific inhibitor that prevents autoactivation of trypsinogen in the pancreas and pancreatic juice [41]. Later studies showed that PSTI was also expressed in some extrapancreatic normal tissues [39,4345] and in various cancers, including pancreatic [34], colorectal [35], gastric [36], lung [37], and hepatocellular [38] cancers. It was found that the serum concentration of immunoreactive PSTI is elevated after surgery, trauma and severe infection [45][46][47], suggesting that PSTI is an acute phase reactant.…”
Section: Controlmentioning
confidence: 99%
“…These phenomena imply that PSTI has other physiological and pathological roles in addition to the inactivation of trypsin. Several papers suggest that tumor-derived PSTI acts as autocrine or paracrine growth factor [46,[50][51][52][53][54], and is associated with the tumor growth of stromal proliferation of fibrous tissues [36,37], although it has been reported recently that the evaluation of tumor-derived PSTI as a paracrine or autocrine growth factor is not definite and needs confirmation [55]. The hPSTI mRNA expression in type II citrullinemia patients was equivalent to the level in hepatic cancer portions (Figs.…”
Section: Controlmentioning
confidence: 99%